2017
DOI: 10.3389/fphar.2017.00375
|View full text |Cite
|
Sign up to set email alerts
|

Erythrodiol, an Olive Oil Constituent, Increases the Half-Life of ABCA1 and Enhances Cholesterol Efflux from THP-1-Derived Macrophages

Abstract: Cholesterol efflux (ChE) from macrophages is an initial step of reverse cholesterol transport (RCT). The ATP-binding cassette transporter A1 (ABCA1) is a key transporter for ChE and its increased expression is regarded to attenuate atherosclerosis. Thus, the identification and characterization of molecules raising ABCA1 and thereby stimulating ChE is of pharmacological relevance. In this study, we tested dietary compounds from olive oil for their capacity of enhancing cellular ABCA1 protein level. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Recently, a study was conducted in THP-1 macrophages to screen the effect of various components of olive oil on foam cell formation. The results showed that among several compounds, only erythrodiol (10 mM) has a positive effect on ApoA-1mediated cholesterol efflux by inhibiting ABCA1 degradation (Wang et al, 2017f). Therefore, erythrodiol may serve as a good candidate for further studies related to the prevention of atherosclerosis progression.…”
Section: B Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study was conducted in THP-1 macrophages to screen the effect of various components of olive oil on foam cell formation. The results showed that among several compounds, only erythrodiol (10 mM) has a positive effect on ApoA-1mediated cholesterol efflux by inhibiting ABCA1 degradation (Wang et al, 2017f). Therefore, erythrodiol may serve as a good candidate for further studies related to the prevention of atherosclerosis progression.…”
Section: B Terpenoidsmentioning
confidence: 99%
“…Increased ApoA-1mediated cholesterol efflux by inhibiting ABCA1 degradation in THP-1 macrophages (Wang et al, 2017f).…”
Section: Erythrodiolmentioning
confidence: 99%
“…It have been also described that hesperetin, a citrus flavonoid, increased ABCA1 promoter and LXR enhancer activities in THP-1 macrophages [ 139 ]. Recently, dietary compounds from olive oil were tested for their capacity to enhance cellular ABCA1 protein level, and authors identified erythrodiol (Olean-12-ene-3b,28-diol) as an ABCA1 stabilizer [ 140 ]. Additionally, the mRNA and protein expression of LXRs and their target genes, including ABCA1 , was significantly increased in macrophages stimulated with cineole [ 141 ].…”
Section: Precision Nutrition and Lipid Metabolism In Colorectal Camentioning
confidence: 99%
“…Emodin, an anthraquinone derivative isolated from the roots of Rheum palmatum , enhanced cholesterol efflux by activating PPARγ in ox-LDL-loaded THP1 macrophages [ 135 ]. Erythrodiol from olive oil promoted cholesterol efflux from THP-1-derived macrophages by stabilizing the ABCA1 protein [ 136 ]. Leoligin, a natural lignan found in Edelweiss ( Leontopodium nivale ssp.…”
Section: Natural Products Regulating Macrophage Cholesterol Efflumentioning
confidence: 99%